PENANGGULANGAN SAMPAH DI ERA COVID 19 DENGAN PENDEKATAN SOSIAL DI LINGKUNGAN BOGEG KELURAHAN BANJAR AGUNG RT 01 RW 02 - Nur Hidayanti; Raden Kania; Tifani Intan Solihati; Rudianto Rudianto; Ramdani Budiman; Ely Nuryani (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Garbage problems are common in every city. However, this can be resolved with various solutions that can overcome these problems. One of them is by conducting field observations, then conducting socialization and social approaches to residents. In this way, the waste problem can be solved little by little. The results of the observations showed that there were piles of garbage in the residents' gardens and the amount of garbage scattered in the waterways due to the absence of trash cans and the difficulty of accessing garbage trucks to transport residents' garbage. Especially in this era of covid 19, we must maintain cleanliness from various viruses. Garbage is a small thing that can trigger a virus to grow. Therefore, a solution was found to overcome the waste. With the solution for making trash cans by KKM students, residents can throw garbage in its place and use an open-top Tossa motorbike because it is small and can enter the narrow road in the bogeg neighborhood of RT 1 RW 2, Banjar Agung village. This is expected to be a solution to the waste problem in the area